2017
DOI: 10.1097/01.ogx.0000526816.16579.d4
|View full text |Cite
|
Sign up to set email alerts
|

24/7 Presence of Medical Staff in the Labor Ward; No Day-Night Differences in Perinatal and Maternal Outcomes

Abstract: (Abstracted from Am J Perinatol 2017;34:529–534) An unavoidable part of every health care professional's life is nighttime shifts that may have negative effects on both the providers themselves and the patients they care for. Absence of experienced staff during the night and exhaustion after long working days could lead to errors and subsequently adverse neonatal and maternal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…However, poor perinatal outcome was not significantly associated with time of delivery. Our results are in line with previous studies [9] although refuted by others from resource limited-settings [10].…”
Section: Discussionsupporting
confidence: 94%
“…However, poor perinatal outcome was not significantly associated with time of delivery. Our results are in line with previous studies [9] although refuted by others from resource limited-settings [10].…”
Section: Discussionsupporting
confidence: 94%
“…Previous literature has shown conflicting evidence in the outcomes of neonates born in the evening and nighttime hours, which may be related to the quality of resuscitation and NRP adherence during these time periods 16 , 17 , 18 , 20 , 21 , 22 , 23 . In this analysis, we used video recordings scored with the mNRA tool to determine if adherence to NRP differed between resuscitations of infants born during daytime, evening, or nighttime hours.…”
Section: Discussionmentioning
confidence: 99%
“…Shift length, off-hours shifts, and physician fatigue have long been implicated as contributors to medical errors and poor outcomes 20 . Several studies have identified no significant temporal variations in rates of intrapartum and neonatal morbidity and mortality 21 , 22 , 23 . However, others have shown that despite higher risk births occurring during daytime hours, infants born at night and during high-volume days and weekends have an increased risk of adverse neonatal complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International wurden in den letzten 5 Jahren divergierende Studienergebnisse zum "Wochenendeffekt in der Geburtshilfe" veröffentlicht: Während nach den Ergebnissen von Hoque und Hoque ihrem Geburtenkollektiv in der Nacht mehr Kinder mit pH-Werten < 7,10 (10,8 gegenüber 6,3 %) geboren wurden [16][17][18]. Und Gijsen et al (2012) berichteten über Ergebnisse einer Registerstudie, die auf der Analyse von 450 000 Geburten in den Niederlanden beruhte.…”
Section: Diskussionunclassified